Kesalahan Pemecahan Masalah Soal Cerita Pecahan pada Peserta Didik Sekolah Dasar: Systematic Literature Review (SLR) - Serlia Nurul Aizzah; Anesa Surya (Universitas Sebelas Maret, 2025)
Problem solving in mathematics, especially fraction word problems, is a challenge for elementary school students which can affect understanding of concepts. This research aims to examine the literature on the forms of errors made by students in solving fraction story problems and the factors that cause them. The method used is Systematic Literature Review (SLR), analyzing scientific articles published between 2015 and 2025, through the Google Scholar database with the keywords: